2020
DOI: 10.1016/j.breast.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Dual HER2 blockade in the first-line treatment of metastatic breast cancer - A retrospective population-based observational study in Danish patients

Abstract: Objectives Randomized clinical trials do not include a population that truly reflects a real-world population, due to their inclusion and exclusion criteria. This leads to concerns about the applicability of these studies in a clinical practice. In the present study, we aim to describe the clinical and demographic characteristics, treatment patterns, and clinical outcomes in a population of patients with HER2-positive metastatic breast cancer who received pertuzumab and trastuzumab as first-line t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…Three population-based single-arm studies, 2 of which used similar population and data sources as the present study, reported poorer realworld OS results compared with the CLEOPATRA trial (OS, 39.2, 41.8, and 43.0 months). [12][13][14] In In the real-world setting, we noted a similar 1-year cumulative incidence of cardiac-related adverse events between the pertuzumab and control groups. A previous Ontario study found 1.8 heart failure events that required hospitalization per 100 person-years among patients who received pertuzumab.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Three population-based single-arm studies, 2 of which used similar population and data sources as the present study, reported poorer realworld OS results compared with the CLEOPATRA trial (OS, 39.2, 41.8, and 43.0 months). [12][13][14] In In the real-world setting, we noted a similar 1-year cumulative incidence of cardiac-related adverse events between the pertuzumab and control groups. A previous Ontario study found 1.8 heart failure events that required hospitalization per 100 person-years among patients who received pertuzumab.…”
Section: Discussionmentioning
confidence: 84%
“…Although some studies found that realworld OS was comparable to trial findings, [9][10][11] other studies reported that median OS was lower than that observed in the trial. [12][13][14] In addition, some studies noted increased cardiac-related adverse events observed in the real-world setting compared with the cardiotoxicity observed in the CLEOPATRA trial. 10,12,15,16 These studies described mainly the survival of patients who received pertuzumab, without exploring the relative incremental survival benefit when pertuzumab treatment was compared with previous standard treatments used in the real world.…”
Section: Introductionmentioning
confidence: 99%
“…Supplemental statistical comparison was done between our cohort (A) and another cohort (B) from a previous DBCG real-world study examining originator trastuzumab and pertuzumab in first-line therapy for HER2-positve mBC. 12 The other real-world study included 291 patients. Hazard ratio (HR) for PFS (A vs B) between the two cohorts was 1.31 (95% CI, 0.98-1.75).…”
Section: Resultsmentioning
confidence: 99%
“…A population-based observational study from the DBCG published in 2020 examined the efficacy of trastuzumab and pertuzumab in first-line treatment of HER2-positive mBC using real-world data from the DBCG database. 12 The study included 291 patients from all departments of oncology in Denmark and had a follow-up period from April 2013 until August 2017. The study showed an mPFS of 15.8 months (95% CI, 14.0-19.9) and mOS of 41.8 months (95% CI, 37.7-NE).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other literature that demonstrated the gap between the efficacy in the clinical trial and the outcomes in the real-world setting, [21][22][23] pertuzumab has also been reported to have lower benefit in the real world compared with the efficacy observed in the trial. [24][25][26] Given these uncertainties regarding the clinical benefit and the wide variation in the economic estimates, there is an impetus for evaluating the cost-effectiveness of pertuzumab using real-world population-based data. Moreover, with the growing interest toward life-cycle health technology assessment by health technology agencies, such as CADTH and NICE, cost-effectiveness studies can also inform the reassessment of funded drugs.…”
mentioning
confidence: 99%